THE INFLUENCE OF NET PROFIT MARGIN, RETURN ON ASSETS, AND RETURN ON EQUITY ON THE SHARE PRICE OF LQ45 COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2020-2023. - Wahyu Sudrajat; Budi Fajrul Muiz; Benny Dhevyanto; Krisdiana Krisdiana (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the effect of Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) on the stock prices of companies listed in LQ45 on the Indonesia Stock Exchange during the period 2020-2023. The main objective of this study is to determine the extent to which these three financial ratios affect stock prices. The method used is multiple regression analysis with secondary data collected from the company's annual report and the official website of the Indonesia Stock Exchange. The results show that NPM has a significant influence on stock prices, while ROA and ROE do not show a meaningful influence. This finding emphasizes the importance of NPM as an indicator of company performance that can attract investors. The conclusion of this study is that companies need to focus on increasing NPM to increase the value of their shares. Future research is recommended to explore other variables that affect stock prices and conduct longitudinal analysis.